2000
DOI: 10.1097/00005392-200008000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Biopsy Protocol Improves the Detection Rate of Prostate Cancer

Abstract: Increasing the number of biopsy cores and improving prostate peripheral zone sampling resulted in a significant improvement in the detection of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 12 publications
4
36
0
1
Order By: Relevance
“…However, the present detection rate of an additional 6% of tumours con®ned exclusively to the lateral PZ compares favourably with Ravery et al [23], who noted a 6.6% overall improvement in prostate cancer detection with the addition of 4 ±6 lateral PZ biopsies, depending on prostate volume. In contrast, Naughton et al [24] found no signi®cant improvement (27% vs 26%) in cancer detection when a 12-core extended biopsy protocol incorporating the lateral PZ was prospectively compared with routine sextant biopsies alone.…”
Section: Discussionsupporting
confidence: 78%
“…However, the present detection rate of an additional 6% of tumours con®ned exclusively to the lateral PZ compares favourably with Ravery et al [23], who noted a 6.6% overall improvement in prostate cancer detection with the addition of 4 ±6 lateral PZ biopsies, depending on prostate volume. In contrast, Naughton et al [24] found no signi®cant improvement (27% vs 26%) in cancer detection when a 12-core extended biopsy protocol incorporating the lateral PZ was prospectively compared with routine sextant biopsies alone.…”
Section: Discussionsupporting
confidence: 78%
“…[6][7][8][9] A review of recent MEDLINE English literature studies that report on complications of transrectal prostate biopsies and list hematochezia as a complication, showed that of 5911 men biopsied only four required admission for observation of hematochezia, three had oversewing of the rectal mucosa within 2 h of the biopsy to stop bleeding and none required transfusion (Table 1). [10][11][12][13][14][15][16][17] This man had an arterial bleeder that opened 5 days after his biopsy; poorly controlled hypertension and the firm bowel movement most likely contributed to the life-threatening hemorrhage. Neovascularization related to his large volume of disease with high Gleason-grade carcinoma may also have contributed to this patient's excessive bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Kelly et al 7 reported a sensitivity for TRUS and CDU, respectively, of 96 and 87%, with only one out of 158 cases of adenocarcinoma not visible with a standard TRUS. Newman et al 8 reported a sensitivity and specificity for malignancies of 49 and 93% emphasizing the necessity of a biopsy, even in patients with a negative CDU.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the extended biopsy scheme of Ravery et al: 5 three cores in each lobe (base, median portion and apex), three cores on the left and right lateral margin of the gland and two additional cores on the transition zone. In the areas where a marked increase in vascularization after the Levovist s injection was visible, further bioptic samples were taken.…”
Section: Methodsmentioning
confidence: 99%